A functional single nucleotide polymorphism of SET8 is prognostic for breast cancer - Liu, Ben (Oncotarget, 2016)
A single-nucleotide polymorphism (SNP) locus rs16917496 (T > C) within the 3′-untranslated region (3′-UTR) of SET8 was associated with susceptibility in several malignancies including breast cancer. To further elucidate the prognostic relevance of this SNP in breast cancer, we conducted a clinical study as well as SET8 expression analysis in a cohort of 1,190 breast cancer patients. We demonstrated the expression levels of SET8 in TT genotype were higher than in CC genotypes, and high levels of SET8 were associated with poor survival. SET8 expression was significantly higher in breast tumor tissue than in paired adjacent normal tissue. In addition, survival analysis in 315 patients showed SNP rs16917496 was an independent prognostic factor of breast cancer outcome with TT genotype associated with poor survival compared with CC/CT genotypes. Thus, this SNP may serve as a genetic prognostic factor and a treatment target for breast cancer. Future studies are warranted.